Bilateral multifocality is an independent predictor of patients’ outcome in Middle Eastern papillary thyroid carcinoma - Parvathareddy, Sandeep Kumar; Siraj, Abdul K.; Annaiyappanaidu, Padmanaban; Siraj, Nabil; Al-Sobhi, Saif S.; Al-Dayel, Fouad; Al-Kuraya, Khawla S. (Frontiers in Endocrinology, 2023)
Background: Tumor multifocality is frequently seen in Papillary thyroid carcinoma (PTC). However, few studies have analysed the impact of bilateral multifocality in PTC. The incidence of bilateral multifocality, its clinico-pathological associations and prognostic impact in PTC from Middle Eastern ethnicity remains unestablished. Methods: We retrospectively evaluated 1283 patients who underwent total thyroidectomy for PTC. Bilateral and unilateral multifocality were decided based on the final pathology result. Primary outcome was recurrence free survival (RFS). Risk factors for bilateral multifocality were analyzed by multivariate logistic regression analysis. Results: Multifocal PTC was found in 54.3% (697/1283) of patients. Among the 697 multifocal PTCs, 210 patients (30.1%) had unilateral multifocal PTC and 487 patients (69.9%) had bilateral multifocality. Bilateral multifocality was significantly associated with older age at diagnosis (p = 0.0263), male gender (p = 0.0201), gross extrathyroidal extension (p = 0.0332), larger primary tumor size (>4cm; p = 0.0002), lateral lymph node metastasis (p = 0.0008), distant metastasis at diagnosis (p = 0.0195) and recurrence (p = 0.0001). Bilateral multifocality was also found to be an independent predictor of RFS (Hazard ratio = 1.58; 95% Confidence Interval = 1.03 – 2.51; p = 0.0360). Multivariate logistic regression analysis demonstrated tumor diameter >4cm to be the only independent risk factors for bilaterality in multifocal PTC (Odds ratio = 2.07; 95% Confidence Interval = 1.32 – 3.26; p = 0.0016). Conclusions: Incidence of bilateral multifocality is high in Middle Eastern PTC. Tumor diameter >4cm can be considered as a predictive factor for bilateral multifocal PTC. Bilateral multifocality appears to be an important prognostic factor for PTC and an independent predictor of RFS. Therefore, patients with bilateral multifocal PTC may benefit from more frequent follow-up to identify recurrences earlier.